The Role of Islamic Boarding Schools in Improving the Quality of Islamic Religious Education at MTs Nurul Qodiri Central Lampung - Afina Nur Aini; Ikhwan Aziz; Suhono Suhono (International Journal on Advanced Science, Education, and Religion, 2024)
Islamic boarding schools have a big role in the world of education, especially in Islamic education. To produce the next generation who are intelligent and have noble morals, comprehensive education is needed, in the sense that it covers all potential from cognitive, affective and psychomotor aspects. Mts Nurul Qodiri is a school institution that is within the scope of the Islamic Boarding School, students at this school do not only come from within the Islamic boarding school, many from the wider community attend MTs Nurul Qodiri. The article aims to analyze the role of islamic boarding schools in improving the quality of islamic religious education at mts nurul qodiri central lampung. The method used field research method (field research) which is descriptive in nature. The research sample is 5 teachers and 10 students. In this research, researchers used several data collection tools, namely through observation, interviews and documentation. This research uses triangulation of sources and methodology to ensure the authenticity of the data. The result shows that there are efforts made by Islamic boarding schools to improve the quality of Islamic religious education in schools, students are becoming more orderly in performing the Duha prayer, routinely reading the Al-Waqiah letter after performing the Duha prayer. Not only are they accustomed to performing Duha prayers, students who study at MTs Nurul Qodiri have the potential to memorize juz amma and have a spirit of good morals. From these efforts the quality of Islamic religious education in schools is increasing. Keywords: Role of Islamic Boarding Schools, Quality Islamic Education